Translucent MXene Oxide–Based Bilayered Nanocoating on Woods for Integrated Active and Passive Fire Safety - Hu, Wen‐Yu; Cao, Cheng‐Fei; Chen, Zuan‐Yu; Hu, Wan‐Jun; Yang, Shihe; Yu, Bin; Chen, Guangming; Ma, Jun; Gao, Jie‐Feng; Tang, Long‐Cheng (Small structures, 2025)
Intelligent fire‐warning materials and sensors have gained considerable attention due to their excellent passive flame resistance and sensitive active fire‐alarm behaviors. However, current nanofiller‐based fire‐warning composites (e.g., MXene, graphene) still face limitations, including intrinsic dark feature, poor structural reliability, and unstable fire‐warning response, hindering their broad use in decorative applications. Herein, a novel MXene derivative‐based bilayered composite nanocoating on wooden substrates with translucent features, exceptional flame resistance, and sensitive fire‐warning response is reported. MXene oxide porous nanoparticles are synthesized by a facile and simple oxidation of MXene and show unexpected network structure and semitransparent feature. Utilizing double‐layer structure and designed cross‐linked interface, the final nanocoatings applied onto the wooden substrates display good mechanical property and tunable optical transparency. Further, such double‐layer design guarantees excellent fire resistance performance through the formation of a compact C/N/P‐dopped TiO2 network during combustion. More interestingly, the resulting composite nanocoatings also display a rapid fire‐responsiveness (≈2.9 s), extended alarm duration (>300 s), and high repeated fire‐alarm capacity (>30 cycles) even after 1 year outdoors. In this work, a novel strategy is provided for designing intelligent semitransparent, fire‐retardant, and fire‐warning coatings for fire safety of wooden architecture. MXene oxide–based translucent bilayered coatings on wood exhibit excellent fire resistance, rapid fire response (≈2.9 s), long alarm duration (>300 s), and over 30 cycles of fire‐alarm capability even after 1 year outdoors. The coatings feature tunable transparency, good mechanical properties, and provide a novel strategy for fire‐retardant MXene coatings in wooden structures.